Transport de marchandises transalpin - Sandra Lange; Flavio V. Ruffini (Revue de Géographie Alpine)
Freight transport in the Alpine space is an ambivalent issue: on the one hand it brings great benefits for individuals and economies on the other hand it brings many negative side effects on quality of life and health. Even if the effects of transport have been investigated and programmes, policies and measures developed, transport still represents an essential challenge for the Alpine countries and requires internationally harmonized action. Against this background the project MONITRAF2 has been elaborated, which aims at developing common measures to reduce the negative effects of road transport and improve the quality of life in the affected transit valleys. This paper addresses central questions of transalpine freight transport: its development and framework conditions, the resulting need for cooperation and action and the responses already given and need to be given for a more sustainable transport within the Alps.